2008
DOI: 10.1111/j.1752-1688.2008.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Sediment Production, Watershed Characteristics, and Land Use in the Tahoe Basin, California‐Nevada1

Abstract: In efforts to control the degradation of water quality in Lake Tahoe, public agencies have monitored surface water discharge and concentrations of nitrogen, phosphorus, and suspended sediment in two separate sampling programs. The first program focuses on 20 watersheds varying in size from 162 to 14,000 ha, with continuous stream gaging and periodic sampling; the second focuses on small urbanized catchments, with automated sampling during runoff events. Using data from both programs, we addressed the questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The watershed characteristics that have been examined include land use and land cover patterns, regional geology, soil characteristics, climate, topography, extent of impervious surface, population density, road density, urbanization pattern, etc. (Ritter, 1986;Battaglin and Goolsby, 1997;McFarland and Hauck, 1999;Arheimer and Liden, 2000;Liu et al, 2000;Ometo et al, 2000;Sliva and Williams, 2001;Smith et al, 2001;Donner, 2003;Meador and Goldstein, 2003;Santos-Roman et al, 2003;Turner and Rabalais, 2003;Carle et al, 2005;Xian et al, 2007;Zampella et al, 2007;Chang, 2008;Coats et al, 2008;Amiri and Nakane, 2009;Atkinson et al, 2009). Understandings of such empirical relationships can help assess conditions of unmonitored water bodies, identify human activities that significantly contribute to pollution as well as critical areas that are at risk, and promote management practices to reduce nonpoint source pollution (McFarland and Hauck, 1999;Gergel et al, 2002;Griffith et al, 2002;Baker, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…The watershed characteristics that have been examined include land use and land cover patterns, regional geology, soil characteristics, climate, topography, extent of impervious surface, population density, road density, urbanization pattern, etc. (Ritter, 1986;Battaglin and Goolsby, 1997;McFarland and Hauck, 1999;Arheimer and Liden, 2000;Liu et al, 2000;Ometo et al, 2000;Sliva and Williams, 2001;Smith et al, 2001;Donner, 2003;Meador and Goldstein, 2003;Santos-Roman et al, 2003;Turner and Rabalais, 2003;Carle et al, 2005;Xian et al, 2007;Zampella et al, 2007;Chang, 2008;Coats et al, 2008;Amiri and Nakane, 2009;Atkinson et al, 2009). Understandings of such empirical relationships can help assess conditions of unmonitored water bodies, identify human activities that significantly contribute to pollution as well as critical areas that are at risk, and promote management practices to reduce nonpoint source pollution (McFarland and Hauck, 1999;Gergel et al, 2002;Griffith et al, 2002;Baker, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Both SRP and TP loads are associated with land development, but PP increases more rapidly than SRP with developed area and total discharge. This is consistent with biogeochemical buffering of SRP concentration (Coats et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In a study of stormwater runoff pollutant concentrations in small developed catchments, Coats et al . () found that the percent of area classed as impervious residential explained 49% of the ln(SRP) discharge‐weighted mean concentration. In the LTIMP dataset, three watersheds have percent developed areas greater than 10%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in land use and land cover (LULC) can alter biotic diversity, primary productivity, surface runoff, water quality, and a host of other attributes associated with terrestrial and aquatic ecosystems (Coats et al, 2008;Wilson and Weng, 2010). LULC change has a significant spatiotemporal relationship with water supply and quality (Somura et al, 2012;Penha et al, 2016).…”
Section: Introductionmentioning
confidence: 99%